Effectiveness of Alberta Family Integrated Care on infant length of stay in level II neonatal intensive care units: a cluster randomized controlled trial - Karen M. Benzies; Khalid Aziz; Vibhuti Shah; Peter Faris; Wanrudee Isaranuwatchai; Jeanne Scotland; Jill Larocque; Kelly J. Mrklas; Christopher Naugler; H. Thomas Stelfox; Radha Chari; Amuchou Singh Soraisham; et al. (BMC, 2020)
Abstract Background Parents of infants in neonatal intensive care units (NICUs) are often unintentionally marginalized in pursuit of optimal clinical care. Family Integrated Care (FICare) was developed to support families as part of their infants' care team in level III NICUs. We adapted the model for level II NICUs in Alberta, Canada, and evaluated whether the new Alberta FICare™ model decreased hospital length of stay (LOS) in preterm infants without concomitant increases in readmissions and emergency department visits. Methods In this pragmatic cluster randomized controlled trial conducted between December 15, 2015 and July 28, 2018, 10 level II NICUs were randomized to provide Alberta FICare™ (n = 5) or standard care (n = 5). Alberta FICare™ is a psychoeducational intervention with 3 components: Relational Communication, Parent Education, and Parent Support. We enrolled mothers and their singleton or twin infants born between 32 0/7 and 34 6/7 weeks gestation. The primary outcome was infant hospital LOS. We used a linear regression model to conduct weighted site-level analysis comparing adjusted mean LOS between groups, accounting for site geographic area (urban/regional) and infant risk factors. Secondary outcomes included proportions of infants with readmissions and emergency department visits to 2 months corrected age, type of feeding at discharge, and maternal psychosocial distress and parenting self-efficacy at discharge. Results We enrolled 654 mothers and 765 infants (543 singletons/111 twin cases). Intention to treat analysis included 353 infants/308 mothers in the Alberta FICare™ group and 365 infants/306 mothers in the standard care group. The unadjusted difference between groups in infant hospital LOS (1.96 days) was not statistically significant. Accounting for site geographic area and infant risk factors, infant hospital LOS was 2.55 days shorter (95% CI, − 4.44 to − 0.66) in the Alberta FICare™ group than standard care group, P = .02. Secondary outcomes were not significantly different between groups. Conclusions Alberta FICare™ is effective in reducing preterm infant LOS in level II NICUs, without concomitant increases in readmissions or emergency department visits. A small number of sites in a single jurisdiction and select group infants limit generalizability of findings. Trial registration ClinicalTrials.gov Identifier NCT02879799 , retrospectively registered August 26, 2016.